A cross-sectional, multivariate, disaggregated study on impact of key drivers of customer satisfaction on brand perception and loyalty in selected hotel chains of India. (1st January 2013) - Padhi, Soumya Ranjan
The key to sustained business performance for any organisation lies undoubtedly with the customer loyalty towards that organisation. But to keep them remain loyal towards the organisation is an important challenge for most of the businesses today across the globe and across the sectors like hotels, banks, etc. The present study views a hotel as an integrated system that needs to be managed and measured to enhance the customer's overall satisfaction to enhance customer loyalty to maximise the hotel's performance. The present study tries to explore: 1) how the overall consumption experience has direct impact on satisfaction; 2) satisfaction in-turn has direct impact on brand perception; 3) how both the satisfaction and brand perception have combined effect on loyalty. Hence, an attempt was made to study the explicit linkages that extend from internal processes to customer satisfaction to customer loyalty. The framework of research is designed to be: multivariate, disaggregated and cross-sectional where the derivation of multivariate models depicts significant strategic value for business unit managers where it acknowledges that key drivers of customer satisfaction may differ across chain affiliated hotels.